2019
DOI: 10.1073/pnas.1914542116
|View full text |Cite
|
Sign up to set email alerts
|

Mutational inactivation of mTORC1 repressor gene DEPDC5 in human gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common human sarcoma and are initiated by activating mutations in the KIT or PDGFRA receptor tyrosine kinases. Chromosome 22q deletions are well-recognized frequent abnormalities in GISTs, occurring in ∼50% of GISTs. These deletions are thought to contribute to the pathogenesis of this disease via currently unidentified tumor suppressor mechanisms. Using whole exome sequencing, we report recurrent genomic inactivated DEPDC5 gene mutations in GISTs (16.4%, 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…121 Recently, Pang et al found that DEPDC5 was a GIST-specific tumor suppressor and TKI treatment response regulator, and was closely related to the development and progression of GISTs. 122 Sequencing of the entire exon showed that DEPDC5 reduced cell proliferation and induced cell cycle arrest through the mTORC1 signaling pathway, but it could lead to the progression of GISTs when it lost function due to inactivation mutation. In addition, DEPDC5 is not only a potential therapeutic target, but also can regulate the sensitivity of GISTs to KIT inhibitors.…”
Section: Novel Molecular Mechanism Of Gistmentioning
confidence: 99%
“…121 Recently, Pang et al found that DEPDC5 was a GIST-specific tumor suppressor and TKI treatment response regulator, and was closely related to the development and progression of GISTs. 122 Sequencing of the entire exon showed that DEPDC5 reduced cell proliferation and induced cell cycle arrest through the mTORC1 signaling pathway, but it could lead to the progression of GISTs when it lost function due to inactivation mutation. In addition, DEPDC5 is not only a potential therapeutic target, but also can regulate the sensitivity of GISTs to KIT inhibitors.…”
Section: Novel Molecular Mechanism Of Gistmentioning
confidence: 99%
“…The SMARCB1/INI1 gene was identified as a potent tumor suppressor in rhabdoid tumors, epithelioid sarcomas, schwannomatosis, synovial sarcomas, and other conditions [17]. Recently, Pang et al reported recurrent genomic inactivated DEPDC5 mutations in GISTs; the mutations were prognostic in that they were associated with aggressive GISTs, GIST progression, and low sensitivity to KIT inhibitors [18]. The loss of tumor suppressor genes in 22q region has yet to be reported in aGCTs.…”
Section: Chromosome Instability In Recurrent Agctsmentioning
confidence: 99%
“…The GATOR1 (26) and KICSTOR (33,34) complexes are negative regulators of mTORC1 activity in the amino acid sensing pathway, which is a key branch within the mTOR network. Mutational inactivation or decreased expression levels of DEPDC5 or NPRL2 have been reported in glioblastoma, ovarian cancer, and gastrointestinal stromal cancer (26,40,41). Loss of GATOR1 complex, the GAP for RagA or RagB, via DEPDC5, NPRL2 or NPRL3 KO should increase levels of GTP-bound RagA or RagB and, therefore, lead to constitutive activation of mTOR (26).…”
Section: The Nutrient-sensing Mtorc1 Pathway Affects Pi3kα Inhibitor Responsementioning
confidence: 99%